Laser-Induced Highly Stable Conductive Hydrogels for Robust Bioelectronics - Yibo Li; Hao Zhou; Huayong Yang; Kaichen Xu (Nano-Micro Letters)
Highlights Stable adhesion of pure poly(3,4-ethylenedioxythiophene):polystyrene sulfonate hydrogel to polymer substrates was successfully achieved via a laser-induced phase separation and adhesion method. The resulting conductive hydrogel exhibits a superior wet electrical conductivity up to 101.4 S cm−1 and a spatial resolution down to 5 μm. Such hydrogels hold great promise in robust bio-interfacing electrodes suitable for long-term high-fidelity signal monitoring.